The Effect of Binder FS-462 and Sky Binder 235 on Color Fastness Resistance in 100% Polyester Printing with Pigment Dyes - Luciana Luciana; Winni Oktaviani (Sainteks: Jurnal Sain dan Teknik, 2022)
The printing with pigment dyes on 100% polyester fabric is one of the materials that can be used to make clothes. Clothing products made with the printing technique must have a good color fastness. In printing with pigment dyes must be mixed with a binder. These binder have different solid content (% glucose). Therefore, the selection of the right binder is very important t produce quality fabrics with good color fastness. The purpose of this study was to determine the value of color fastness to washing and rubbing and the value of color differences in the printing process with pigment dyes on 100% polyester fabrics and to determine which binder had the best results. The method of this study used is an experiment with a lab scale. After experimenting with the printing process using the Binder FS-462 and Sky Binder 235, a test was conducted which stated that Binder FS-462 was the binder that had the best results. The test values ​​were obtained as follows, color fastness to washing on dark colors 4-5 for staining scale and 4 for grey scale, color fastnes to rubbing on dark colors 4 for dry and 2-3 for wet. The factory standard is for color fastness to washing 3 for staining scale and 4 for grey scale, color fastness to rubbing 3-4 for dry and 2-3 for wet, and color difference values ​​>1.